Kepatuhan Penggunaan Obat Hipertensi Pada Lansia Dengan Penyakit Hipertensi Di Dusun Ngagrok Desa Tempel Krian Sidoarjo - atina khoirunnisa; Fahmi Ardianti; Valiandri Puspadina (Jurnal Farmasi Indonesia AFAMEDIS, 2023)
Hypertension is a condition where there is an increase in systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg according to JNC-7 criteria. Hypertension is found most in the population aged over 65 years with a percentage of 60-70%. The purpose of this study was to determine the level of adherence to the use of hypertension drugs in the elderly with hypertension in Dusun Ngagrok, Tempel Krian Village, Sidoarjo. This research is a quantitative research with a descriptive research design. The sample in this study amounted to 58 respondents obtained using a total sampling technique and using a measuring tool in the form of the MARS-5 questionnaire. The results of this study obtained 39 respondents (67.2%) of respondents with a questionnaire value of 25 which means the level of adherence to taking hypertension medication in the elderly who suffer from hypertension in Dusun Ngagrok Tempel Village is included in the high compliance category